Nanoemulsion of Sideroxylon obtusifolium as an Alternative to Combat Schistosomiasis - Rangel, Leonardo da Silva; Passos de Oliveira, Adriana; Falcão, Deborah Quintanilha; Santos, Marcelo Guerra; Von Ranke, Natalia Lindimar; Rodrigues, Carlos Rangel; Santos, José Augusto Albuquerque dos; Rocha, Leandro; Faria, Robson Xavier (Frontiers in Plant Science, 2022)
Schistosomiasis mansoni is caused by the intestinal parasite Schistosoma mansoni. The individuals affected by schistosomiasis have in common that all of them were exposed to aquatic environments contaminated with Schistosoma cercariae that emerged from the infected intermediate host mollusk of the genus Biomphalaria. The WHO recommends using molluscicidal products to reduce the snail population and disease transmission. The WHO encourages the search for alternative substances in schistosomiasis control. Natural products are seen as a promising alternative because they are abundant in countries where schistosomiasis is endemic and have many different substances in their extracts, impairing cases of resistance. Therefore, the nanoemulsion effect of a butanol-soluble fraction of Sideroxylon obtusifolium leaves was evaluated against adults and young Biomphalaria glabrata, spawning of the host mollusk, and infectious larvae of the parasite. Extract-SOB (butanol fraction) and Nano-SOB (nanoemulsion) demonstrated promising activity in adult Biomphalaria glabrata population control with LC50: 125.4 ppm and LC90: 178.1 ppm and LC50: 75.2 ppm and LC90: 97 ppm, respectively. Nano-SOB presented greater potency against young B. glabrata with LC90: 72.1 ppm and LC50: 58.3 ppm. Still relevant activity against S. mansoni cercariae was eliminated in 4 hours (LC90: 34.6 ppm). Nano-SOB reduced viable spawning by approximately 30% at 178.1 ppm and 97 ppm. Concerning the majority substances from this extract, quercetin-3-rhamnosyl-(1-6)-galactoside and hyperoside may cause low ambiental toxicity and human toxicity according to in silico analysis. Thus, Nano-SOB is a promising agent to combat B. glabrata population growth and schistosomiasis transmission.